Implementasi Penggunaan Google Classroom dalam Mata Kuliah PAI Pada Masa Covid-19 - Ahmad Nurfadel; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2022)
The online learning of the lecturers at the campus has determined the applications used in conducting online learning, such as the Google Classroom application used in Islamic Religious Education courses, Google Classroom is used as an online learning solution during the Covid-19 period. The purpose of the study was to determine the use planning, implementation, and evaluation results of the use of Google Classroom as an online learning tool during the Covid-19 pandemic in the Islamic Religious Education course at Tamansiswa Padang University. The research method is qualitative with a case study descriptive approach. The results of the study, based on observations made about the evaluation of plans that have been prepared by lecturers in conducting lectures using the Google Classroom application, are currently said to be successful because this media is very helpful in planning learning in one semester. The conclusion of this research is that in planning the lecturers in carrying out these online learning activities, the lecturer prepares RPS for the tasks given later and also prepares video tutorials, for the media used.